Подолання польсько-українських стереотипів у політичних концепціях паризької «Kultury» - Сенич, Марія; Senych, M. (Волинський національний університет імені Лесі Українки, 2012)
Оцінка Волинської трагедії 1943 р. тісно пов’язана з подоланням міжнаціональних стереотипів, які сформувалися протягом століть спільної історії. Негативні стереотипи формувалися в процесі міжнаціонального протистояння, були причиною наступних польсько-українських конфліктів та становлять загрозу процесові примирення. Великі заслуги у виясненні складних сторінок польсько-українських відносин належить колективові паризької «Kultury». Подолання стереотипів стало важливим фактором міжнаціонального примирення. The reassessment of Volhynian tragedy is closely connected with overcoming of interethnic stereotypes that had formed in the course of common history. Negative stereotypes that emerged in the process of interethnic confrontations were the cause for subsequent Polish-Ukrainian conflicts and contradictions and posed a threat for successful reconciliation process. The team of Parisian journal «Kultura» has performed great services for clarification of complicated periods in Polish-Ukrainian relationship. Overcoming of stereotypes and national hatred has become an important factor in Polish-Ukrainian reconciliation.
Overcoming of Polish-Ukrainian Stereotypes in Political Concepts of Parisian «Kultura»
Keywords: Волинська трагедія; міжнаціональні стереотипи; польсько-український конфлікт; польсько-українське примирення; «Kulturа»; Volhynian tragedy; interethnic stereotypes; Polish-Ukrainian conflict; Polish-Ukrainian reconciliation; «Kulturа»